Dyskopatia kręgosłupa w odcinku lędźwiowym u 10 - letniego dziecka - opis przypadku = Discopathy of the lumbar spine in a 10 - years old child - case study - Woźniak, Kamila; Ratuszek-Sadowska, Dorota Małgorzata; Śniegocki, Maciej (Journal of Education, Health and Sport, 2015)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Śniegocki Maciej. Dyskopatia kręgosłupa w odcinku lędźwiowym u 10 - letniego dziecka - opis przypadku = Discopathy of the lumbar spine in a 10 - years old child - case study. Journal of Education, Health and Sport. 2015;5(9):351-362. ISSN 2391-8306. DOI10.5281/zenodo.30934 http://dx.doi.org/10.5281/zenodo.30934 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A351-362 https://pbn.nauka.gov.pl/works/624249 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 12.09.2015. Dyskopatia kręgosłupa w odcinku lędźwiowym u 10 - letniego dziecka - opis przypadku Discopathy of the lumbar spine in a 10 - years old child - case study Kamila Woźniak1, Dorota Ratuszek-Sadowska2, Maciej Śniegocki1 1. Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu, Polska Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Poland 2. Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu, Polska 2.Chair and Department of Rehabilitation Medicine, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Poland Streszczenie Dyskopatia lędźwiowa stanowi niezwykle rzadki problem występujący u dzieci i młodzieży. W 1945 roku Wahren przedstawił pierwszy opis dotyczący dyskopatii kręgosłupa w odcinku lędźwiowo - krzyżowym u dziecka. Dyskopatia lędźwiowa w populacji pediatrycznej występuje niezmiernie rzadko, a jeszcze rzadziej wymaga interwencji operacyjnej. Powszechnie uważa się, że czynnikami predysponującymi do występowania dyskopatii w odcinku lędźwiowo - krzyżowym w populacji pediatrycznej są dyscypliny sportowe związane ze zwiększonym ryzykiem urazu lub nadmiernymi obciążeniami kręgosłupa, otyłość, wysoki wzrost, przebyty uraz okolicy lędźwiowo – krzyżowej. Dyskopatia u dzieci i młodzieży wykazuje pewne cechy charakterystyczne różniące ją od dorosłych. W literaturze światowej istnieje wiele prac dotyczących metod postępowania w leczeniu dyskopatii kręgosłupa w populacji pediatrycznej, ale nie ma jednoznacznych wytycznych dotyczących kwalifikacji chorych do leczenia operacyjnego. Autorzy przedstawiają opis przypadku klinicznego: 10 - letniego chłopca operowanego z powodu wypukliny jądra miażdżystego w przestrzeni L5/S1. Leczenie chirurgiczne dyskopatii kręgosłupa w odcinku lędźwiowo - krzyżowym u dzieci i młodzieży jest metodą, uzasadnioną tylko wtedy, gdy leczenie zachowawcze okaże się nieskuteczne. Z drugiej strony w przypadku ewidentnego braku efektywności leczenia zachowawczego, nie należy zbyt długo zwlekać z decyzją o podjęciu leczenia operacyjnego. W populacji pediatrycznej wybór metody leczenia i kwalifikacja do leczenia chirurgicznego musi wynikać każdorazowo z wnikliwej analizy każdego przypadku. Słowa kluczowe: dyskopatia, odcinek lędźwiowy kręgosłupa, przepuklina krążka międzykręgowego, populacja pediatryczna, fenestracja. Abstract Lumbar discopathy is a rare clinical problem for children and adolescents. The first description of lumbosacral discopathy was presented in 1945 by Wahren. Lumbar intervertebral discs problem in the pediatric population is extremely rare, and even more rarely requires surgical intervention. It is widely believed that the predisposing factors for the occurrence of disc herniation in the pediatric population are practicing some sports associated with an increased risk of injury or overloads of the spine, obesity, high growth, previous lumbosacral trauma. Intervertebral discs in children and adolescents exhibit certain characteristics that differ from the adults. In the world literature there are many papers about methods of treatment of spinal disc disease in the pediatric patients, but there are no clear guidelines for the selection of patients for surgery. The authors present clinical case: 10-year-old boy operated because of herniation nucleus pulposus at the L5 / S1 level. Taking into account the above facts, it is concluded that surgical treatment in children and adolescents is a method justified only when conservative treatment proves ineffective. On the other hand, dangerous for the patient is the long delay in making a decision about surgery in a situation of obvious inefficiencies conservative treatment, because especially in the pediatric population choice of treatment and classification for surgical treatment must result in each case with careful analysis of each case. Key words: discopathy, lumbar spine, intervertebral disc herniation, pediatric population, fenestration.